OPTIMALISASI LAYANAN TEKNOLOGI INFORMASI MELALUI PENGEMBANGAN SIPINTER (SISTEM PORTAL INFORMASI TERINTEGRASI) DI SMPN 2 TELAGA BERBASIS DOMAIN ITIL - Utiarahman, Alya Pratiwi; Idris, Mohamad Reza Putra Faren; Lasimpala, Muslimin; Budiman, Nurul Rezkiah; Noho, Sri Wina; Bonde, Nazwa Putri Ramadani (TRANSFORMASI, 2026)
SMPN 2 Telaga faces three main problems in information technology service management, namely manual recording of student and teacher attendance, the absence of official digital information media, and reactive management of internet network disruptions without standardized technical guidelines. This research was conducted to build SIPINTER (Integrated Information Portal System) as the main IT serice solution, using the framework of the ITIL (Information Technology Infrastructure Library) framework with five domains namely Service Strategy, Service Design, Service Transition, Service Operation, and Continual Service Improvement. The data collection process was carried out through direct observation and interviews with school stakeholders consisting of the principal, operators, and teachers. This system was developed web-based with main features including a school information portal, QR Code-based digital attendance and GPS location validation, digital teacher permission applications, as well as internet network guidance and complaints. The system was tested using the Black Box Testing method on 9 test scenarios showing that all features were valid. The evaluation showed an increase in the efficiency of attendance recording time from 8-10 minutes to 1-2 minutes, and all service Key Performance Indicators were met. The comprehensive application of the ITIL framework in the development of a junior high school portal is a new contribution in this research that differentiates it from previous research that generally only focuses on the technical aspects of system development.  Keywords : School Portal, Information Technology Infrastructure Library, IT Service Management, Digital Attendance, Information System   SMPN 2 Telaga dihadapkan pada tiga permasalahan utama dalam manajemen layanan teknologi informasi yakni pencatatan absensi siswa dan guru yang masih dilakukan secara manual, ketiadaan media informasi digital resmi, serta pengelolaan gangguan jaringan internet yang bersifat reaktif tanpa panduan teknis terstandarisasi. Penelitian ini dilakukan untuk membangun SIPINTER (Sistem Portal Informasi Terintegrasi) sebagai solusi layanan TI utama, dengan menggunakan kerangka dari framework ITIL (Information Technology Infrastructure Library) lima domain, yaitu Service Strategy, Service Design, Service Transition, Service Operation, dan Continual Service Improvement. Proses pengumpulan data dilakukan dengan observasi dan wawancara langsung dengan stakeholder sekolah yang terdiri atas kepala sekolah, operator, dan guru. Sistem ini dikembangkan berbasis web dengan fitur utama mencakup portal informasi sekolah, absensi digital berbasis QR Code dan validasi lokasi GPS, pengajuan izin guru secara digital, juga panduan dan pengaduan perbaikan jaringan internet. Pengujian terhadap sistem dilakukan dengan metode Black Box Testing terhadap 9 skenario uji menunjukkan seluruh fitur berstatus valid. Evaluasi yang dilakukan menunjukkan peningkatan efisiensi waktu pencatatan absen dari 8-10 menit menjadi 1-2 menit, dan seluruh indikator Key Performance Indicator layanan terpenuhi. Dengan penerapan kerangka dari framework ITIL secara menyeluruh dalam pengembangan portal sekolah tingkat menengah pertama merupakan kontribusi baru dalam penelitian ini yang membedekannya dari penelitian sebelumnya yang umumnys hanya berfokus pada aspek teknis pengembangan sistem Kata kunci : Portal Sekolah, ITIL, Manajemen Layanan TI, Absensi Digital, Sistem Informasi